Investigating the impact of the surface on the physical stability of drug: polymer amorphous solid dispersions - Mushtaq, Rayan (2021)
The formulation of drugs in the amorphous state offers potential advantages, including enhanced apparent solubility and hence bioavailability, although this comes at the cost of instability for recrystallisation. Recently, the importance of surface-enhanced crystallisation (SEC) mechanism on five amorphous drugs has been identified, in which crystal growth at an exposed surface is several orders of magnitude faster than growth in the bulk, and this occasionally affects the crystallisation polymorph and morphology at the surface. The aim of this thesis is to investigate the effect of the surface on the stability of other amorphous APIs against recrystallisation. If a different stability is seen, then these studies are to be extended to examine the influence of the SEC mechanism on the physical stability in the presence or absence of polymer additives.